Is the Natural Instinct to Oviposit in Mated Female Oriental Fruit Fly, Bactrocera dorsalis More of a Brain-Independent Act? - Vyas, Meenal; Parepally, Saravan Kumar; Kamala Jayanthi, Pagadala Damodaram (Frontiers in Physiology, 2022)
Selfish instincts are turned on the moment a female is gravid, be it higher order organisms or lower order organisms like insects. The urge to pass on the gene pool to next generation probably is the driving force. What physiological and neuro-molecular changes control the female oviposition behaviour post-mating in insects? The molecular changes that occur in a gravid female insect are difficult to dissect out considering the distinct behavioural patterns displayed by different insect groups. To understand the role of the brain center in Oriental fruit fly, Bactrocera dorsalis oviposition, egg laying behaviour was analyzed in γ- octalactone exposed, decapitated mated B. dorsalis females. Interestingly, the females displayed a possible urge to oviposit, suggesting a natural instinct to pass on the gene pool. Expression analysis of certain genes involved in oviposition behaviour was also carried out in these insects to explore the molecular aspects of such behaviour. This study tries to assess the involvement of brain center in egg laying and also explore the role of certain neurotransmitter related receptors in decapitated B. dorsalis oviposition behaviour.